Determining important factors of arithmetic skills among newborn babies’ at Malaysian taska using artificial neural network - Kharuddin, Azrul Fazwan; Ahmad Kamaruddin, Saadi; Kamari, Muhamad Naim; Mustafa, Zaida; Azid, Norazura (Southeast Asia Early Childhood Journal, 2018)
In Malaysia, most parents prefer to choose registered early childhood learning centers (TASKA), due to their perceptions that the centers are with quality services and well-observed by the government authority. In this quantitative research, the main objective is to identify the best model to represent the contributing factors which influence arithmetic performance among children at registered Malaysian TASKA. Childrens’ arithmetic performance in general affect their mental capability and overall personal skills development. This research is significant to determining the important contributing factors which influence newborn babies’ mathematical skills. Data was collected using a survey questionnaire. Based on the right sampling method, 376 registered TASKAs in Malaysia were chosen. Among the 458 chosen centers, only 63 centres provide care and education services for children age of 0 to 6 months. Neural network technique was the analysis adapted in order to achive the research objective. In the near future, the research will be extended to the unregistered TASKA in Malaysia, and the fair comparisons will be made with the registered centers.